Pigtail Catheter: A Less Invasive Option for Pleural Drainage in Egyptian Patients with Recurrent Hepatic Hydrothorax - Mohamed Sharaf-Eldin; Adel Salah Bediwy; Abdelrahman Kobtan; Sherief Abd-Elsalam; Ferial El-Kalla; Loai Mansour; Walaa Elkhalawany; Mohamed Elhendawy; Samah Soliman (Gastroenterology Research and Practice)
Background and Aims. Treatment of hepatic hydrothorax is a clinical challenge. Chest tube insertion for hepatic hydrothorax is associated with high complication rates. We assessed the use of pigtail catheter as a safe and practical method for treatment of recurrent hepatic hydrothorax as it had not been assessed before in a large series of patients. Methods. This study was conducted on 60 patients admitted to Tanta University Hospital, Egypt, suffering from recurrent hepatic hydrothorax. The site of pigtail catheter insertion was determined by ultrasound guidance under complete aseptic measures and proper local anesthesia. Insertion was done by pushing the trocar and catheter until reaching the pleural cavity and then the trocar was withdrawn gradually while inserting the catheter which was then connected to a collecting bag via a triple way valve. Results. The use of pigtail catheter was successful in pleural drainage in 48 (80%) patients with hepatic hydrothorax. Complications were few and included pain at the site of insertion in 12 (20%) patients, blockage of the catheter in only 2 (3.3%) patients, and rapid reaccumulation of fluid in 12 (20%) patients. Pleurodesis was performed on 38 patients with no recurrence of fluid within three months of observation. Conclusions. Pigtail catheter insertion is a practical method for treatment of recurrent hepatic hydrothorax with a low rate of complications. This trial is registered with ClinicalTrials.gov Identifier: NCT02119169.